Effects of audio annotation and presentation order in the utilization of non-financial information by individual investors - Ang, Hui Shan (2008)
This study investigates whether (1) supplementing corporate disclosure presentations with audio annotation and (2) varying the presentation order of financial and non-financial information increase the utilization of non-financial information.